Examination of Force Discrimination in Human Upper Limb Amputees With Reinnervated Limb Sensation Following Peripheral Nerve Transfer - Sensinger, Jonathon W.; Schultz, Aimee E.; Kuiken, Todd A. (IEEE transactions on neural systems and rehabilitation engineering, 2009)
Artificial limbs allow amputees to manipulate objects, but the loss of a limb severs the sensory link between a subject and objects they touch. A novel surgical technique we term targeted reinnervation (TR) allows severed cutaneous nerves to reinnervate skin on a different portion of the body. This technique provides a physiologically appropriate portal to the sensory pathways of the missing limb through the reinnervated skin. This study quantified the ability of three amputee subjects who had undergone TR surgery on the chest (two subjects) and upper arm (one subject) to discriminate changes in graded force on their reinnervated skin over a range of 1-4 N using a stochastic staircase approach. These values were compared to those from sites on their intact contralateral skin and index fingers, and from the chests and index fingers of a control population ( n =10) . Weber's ratio (WR) was used to examine the subjects' abilities to discriminate between a baseline force and subsequent forces of different magnitudes. WRs of 0.22, 0.25, and 0.12 were measured on the reinnervated skin of the three TR subjects, whereas WRs of 0.25, 0.23, and 0.12 were measured on their contralateral skin. TR subjects did not have substantially different WRs on their reinnervated versus their contralateral normal side and did not appear to exhibit a trend towards impaired sensation. No significant difference was found between the WR of the chest and index finger of the control subjects, which ranged between 0.09 and 0.21. WR of reinnervated skin for TR subjects were within the 95% confidence interval of the control group. These data suggest that subjects with targeted reinnervation have unimpaired ability to discriminate gradations in force.